(untitled) (UNIZIK Journal of Marketing, 2025)
This study sought to unveil the marketing practices of megachurches in Nigeria. The paper in particular, seeks to ascertain the influence of Pastors’ message, worship centers ambience, church promotion activities and Pastors’ people management style on church attendance. This study adopts a quantitative research design. The study population consist of the entire Pentecostal church members in Yenegoa metropolis, Bayelsa state. Members of Living Faith Church and Salvation Ministries Yenegoa were the accessible population. Three hundred copies of the research instrument were administered while 230 copies were retrieved. Using SPSS 26, the collated data were analyzed with descriptive statistics while the formulated hypotheses were tested with one-way ANOVA, Pearson correlation and simple linear regression at 5% level of significance. The study reveals that all the drivers of church attendance has positive and significant influence on church attendance. Moving forward, the paper recommends among others that churches discourage the use of doubtful and deceitful testimonies to attract members. The paper concludes that church deployment of marketing principles would enable it achieve its growth objective.